0
$\begingroup$

I am reading a section on Boolean algebra in a text book and trying to understand a solution to simplifying problem they have presented.the expression

$$(¬p ∧ ¬q ∨ p)$$

is simplified to $$(¬q ∧ p).$$

I have not been able to work out what law was used t o arive at this. Thanks in advance. PS I am very new to Boolean algebra in case you couldn't tell.

$\endgroup$
1
$\begingroup$

Are you sure that the result is what you wrote?

because I am getting this as $$p \lor \lnot q$$

The procedure is very simple:

We have this expression $$\left(\lnot p \land \lnot q\right) \lor p$$ By the distributive law : => You can find about it here: Laws of boolean algebra

We get : $$\left(p \lor \lnot p \right) \land \left(p \lor \lnot q \right)$$ In the same link above we can find that $ p \lor \lnot p = 1$ then: $$1 \land \left(p \lor \lnot q \right)$$ Again from the link we get: $$p \lor \lnot q$$

Good luck!

$\endgroup$
0
$\begingroup$

By the second distributive law $$ (x y +z )=(x+z)(y+z)$$ or, in $∧ , ∨ $ notation, $$(x∧y∨z)=((x∨z)∧(y∨z))$$ is $$(¬p ∧ ¬q ∨ p)=(¬p ∨ p ) ∧ (¬q ∨ p)=\quad1∧ (¬q ∨ p )= (¬q ∨ p). $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.